DIABETES AND PERIODONTITIS: PROTOCOL FOR DENTAL MANAGEMENT OF PATIENTS WITH DIABETES MELLITUS - de Aquino, Roberta Rocha; Silva, Emilly Rodrigues Machado; Abreu, Julia de Almeida; Menezes, Karine Poleto; Camargo, Gabriela Alessandra da Cruz Galhardo (Seven Editora, 2025)
Diabetes Mellitus represents one of the greatest global public health challenges, with significant impacts on various areas of health, including oral health. Scientific evidence demonstrates a bidirectional relationship between diabetes and periodontal disease, with diabetic patients being three times more likely to develop periodontitis. This article aimed to address, through a narrative review, relevant information regarding dental care for individuals with diabetes, considering the main pathophysiological aspects, oral manifestations, and clinical and therapeutic approaches. A search was conducted in electronic databases such as Google Scholar and PubMed using the descriptors: “Diabetes Mellitus,” “Periodontal Disease,” “Oral Health,” and “Dental Care.” The content was structured into a clinical protocol intended for healthcare professionals, especially dental surgeons, with guidelines based on updated recommendations. The protocol covers aspects ranging from medical history and diagnosis to specific recommendations on pharmacological therapy, anesthetic management, emergency care, and the importance of a multidisciplinary approach. The application of these guidelines can optimize dental care, prevent systemic complications, and improve the quality of life of patients with diabetes.